The Analysis of Implicit Premises within Children’s Argumentative Inferences - Greco, Sara; Perret-Clermont, Anne-Nelly; Iannaccone, Antonio; Rocci, Andrea; Convertini, Josephine; Schär, Rebecca Gabriela (Informal Logic, 2018)
This paper presents preliminary findings of the project [name omitted for anonymity]. This interdisciplinary project builds on Argumentation theory and developmental sociocultural psychology for the study of children’s argumentation. We reconstruct children’s inferences in adult-child and child-child dialogical interaction in conversation in different settings. We focus in particular on implicit premises using the Argumentum Model of Topics (AMT) for the reconstruction of the inferential configuration of arguments. Our findings reveal that sources of misunderstandings are more often than not due to misalignments of implicit premises between adults and children; these misalignments concern material premises rather than the inferential-procedural level.